Comparative approaches to statutory interpretation in civil law and common law jurisdictions - Carney, Gerard (Oxford University Press, 2014)
This article attempts to identify how differently a common law lawyer in a Westminster system and a civil law lawyer in France might interpret statutory provisions. The key to understanding the difference is how the doctrine of separation of powers operates within each of their jurisdictions. There is a considerable difference in this respect. Common law lawyers and judges are expected to supplement statutory law by reference to the common law when this is intended or is needed to make sense of the statute. French civil lawyers, on the other hand, are expressly denied this role, being confined solely to the elucidation of the legislative intent. They are prohibited from filling any ‘gaps’ in the law simply because there are no gaps and because the statute is intended to be comprehensive. Despite the fact that there is a considerable difference in this respect, the principles of statutory interpretation bear a remarkable resemblance. Yet, in their application, differences are likely to emerge because of the starkly contrasting roles of the judiciary. But any assessment of that difference is hard to measure in view of the brevity of civil law judgments, particularly in France